Selection for muscling in swine and its effect on carcass traits - J D Wheat; Donald H Kropf; C H Chang; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1974)
Line differences in weight, litter size at different ages, and in age, loin eye area, and backfat thickness of pigs (adjusted to 200 pounds live weight) were not significant. Sex differences in weight and backfat thickness were significant. Dam groups of progeny differed significantly (P<.0l) in-weights at birth and at 14 and 28 days old and in age, loin eye area, and backfat thickness adjusted to 220 pounds live weight. Hams produced by barrows in the select line were significantly (P<.0l) darker and firmer than those from barrows in the control line.; Swine Day, Manhattan, KS, November 14, 1974
Keywords: Swine day; 1974; Kansas Agricultural Experiment Station contribution; no. 483; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 221; Swine; Muscling; Carcass traits; Weight; Backfat